Fasciculation frequency at the biceps brachii and brachialis muscles is associated with amyotrophic lateral sclerosis disease burden and activity. Issue 2 (2nd December 2020) - Avidan, Reuven; Fainmesser, Yaara; Drory, Vivian E.; Bril, Vera; Abraham, Alon
Abstract: Introduction: Fasciculations are most commonly seen in the biceps brachii muscle in amyotrophic lateral sclerosis (ALS). In this study we have explored the association between fasciculation frequency in a single location—biceps brachii and brachialis muscles (BB), and disease burden and activity. Methods: Sonographic muscle studies were performed in 90 ALS patients, 47 of whom were seen in subsequent follow‐up. The association between fasciculations frequency at the BB and ALS Functional Rating Scale—Revised (ALSFRS‐R) and manual muscle testing (MMT) scores was determined. Results: High fasciculation frequency at the BB, where detection rate was the highest, was associated with shorter disease duration, greater muscle thickness, higher MMT scores, and faster rate of decline in ALSFRS‐R initially, and MMT subsequently. Discussion: High fasciculation frequency at the BB as determined by sonography, is associated with less impairment at time of examination, and a more active disease with a more rapid progression.